Hypoxic-ischaemic encephalopathy: early and late magnetic resonance imaging findings in relation to outcome. Issue 3 (November 1996) - Rutherford, M; Pennock, J; Schwieso, J; Cowan, F; Dubowitz, L
Abstract : Sixteen infants with hypoxic-ischaemic encephalopathy (HIE) were studied using serial magnetic resonance imaging (MRI) up to the age of 2 years. The infants had regular neurological and developmental assessments. An nuclear magnetic resonance (NMR) score was devised to quantify the early and late MRI findings and a neurological optimality score was used to quantify abnormal neurological signs at the time of the final examination. The follow up MRI score was compared with the neonatal MRI score and the outcome of the child. There was a strong positive correlation between the neonatal and follow up MRI scores and between MRI scores and optimality score. All infants with a normal outcome had patchy white matter abnormalities. All infants with an abnormal outcome had extensive white matter abnormalities. The outcome was most severe in those infants with additional basal ganglia atrophy with or without cyst formation. Infants with mild HIE who are developmentally normal at the age of 2 years do not have normal MRI scans and may be at risk of minor neurological problems by school age. Bilateral basal ganglia abnormalities are associated with severe developmental delay, but infants with mainly white matter and cortical abnormalities have less severe problems despite extensive tissue loss.